Overview of Risk Factors and Clinical Outcomes of Pregnancy with COVID-19 in 2019-2020 in Several Asian Countries - Nathanael T. Tarore; Mayer F. Wowor; Glady I. Rambert (Universitas Sam Ratulangi, 2022)
Abstract: Pregnant women are vulnerable to be infected with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) due to changes in the anatomy and physiology of the body. Mortality of pregnant women differs by country and can be affected by risk factors. This study aimed to determine the risk factors and outcome of pregnant women with COVID-19 in several Asian countries. This was a literature review study using three databases namely Pubmed, Science Direct, and Google Scholar. The keywords were â€œMaternalâ€ OR â€œPregnancyâ€ OR â€œPregnanciesâ€ AND â€œCOVID-19â€ OR â€œCoronavirus Disease 2019â€ AND â€œOutcomeâ€ AND â€œRisk Factorâ€. Overall, the most common risk factors were hypertension (10.6%), followed by hypothyroidism (8.1%), diabetes (7.7%), obesity (3.8%) and asthma (1.3%). The majority of patients were above 30 years of age and had gestational age at the 3rd trimester. As many as 70.5% of patients were asymptomatic and had only mild symptoms. Qualitatively, the highest mortality rates were found in Iran (4%), followed by Pakistan (2.1%), India (1.74%), Japan (1.3%), and Saudi Arabia (0.5%). Meanwhile, China, Kuwait, Singapore, and South Korea reported no deaths. In conclusion, the most common risk factor was hypertension and the most common clinical outcome was asymptomatic and had mild symptoms.Keywords: COVID-19; pregnant women; risk factor; clinical outcomesÂ Abstrak: Wanita hamil merupakan kelompok rentan terinfeksi severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) dikarenakan terjadinya perubahan anatomi dan fisiologik tubuh. Mortalitas wanita hamil berbeda pada tiap negara dan dapat dipengaruhi oleh fakor risiko. Penelitian ini bertujuan untuk mengetahui gambaran faktor risiko dan luaran klinis kehamilan dengan COVID-19 pada beberapa negara Asia. Jenis penelitian ialah suatu literature review dengan menggunakan tiga database yaitu Pubmed, Science Direct, dan Google Scholar. Kata kunci yang digunakan ialah â€œMaternalâ€ OR â€œPregnancyâ€ OR â€œPregnanciesâ€ AND â€œCOVID-19â€ OR â€œCoronavirus Disease 2019â€ AND â€œOutcomeâ€ AND â€œRisk Factorâ€ Secara keseleruhan faktor risiko yang terbanyak ialah hipertensi (10,6%), diikuti hipotiroid (8,1%), diabetes (7,7%), obesitas (3,8%), dan asma (1,3%). Mayoritas pasien berusia di atas 30 tahun dan usia kehamilan pada trimester 3. Sebanyak 70,5% pasien bermanifestasi asimtomatis dan bergejala ringan. Secara kualitatif angka mortalitias paling tinggi ditemukan di Iran (4%), diikuti Pakistan (2,1%), India (1,74%), Jepang (1,3%), dan Arab Saudi (0,5%). Cina, Kuwait, Singapura, dan Korea Selatan melaporkan tidak ada kasus kematian. Simpulan penelitian ini ialah faktor risiko yang paling umum ditemukan berupa hipertensi dan luaran klinis yang paling umum ditemukan berupa asimtomatis dan bergejala ringan.Kata kunci: COVID-19; wanita hamil; faktor risiko; luaran klinis